(untitled) (Journal of Parents and Teachers, 1996)
Educational activities focused on peace, such as theater, toy exchanges and readings, are proposed to promote non-violence in the classroom. The decoration of spaces with symbols of peace and the participation of the educational community are essential. These initiatives seek to address violence and promote a peaceful environment in education.